Using FRAM to explore sources of performance variability in intravenous infusion administration in ICU: A non-normative approach to systems contradictions. (July 2020) - Furniss, Dominic; Nelson, David; Habli, Ibrahim; White, Sean; Elliott, Matthew; Reynolds, Nick; Sujan, Mark
Abstract: Systems contradictions present challenges that need to be effectively managed, e.g. due to conflicting rules and advice, goal conflicts, and mismatches between demand and capacity. We apply FRAM (Functional Resonance Analysis Method) to intravenous infusion practices in an intensive care unit (ICU) to explore how tensions and contradictions are managed by people. A multi-disciplinary team including individuals from nursing, medical, pharmacy, safety, IT and human factors backgrounds contributed to this analysis. A FRAM model investigation resulting in seven functional areas are described. A tabular analysis highlights significant areas of performance variability, e.g. administering medication before a prescription, prioritising drugs, different degrees of double checking and using sites showing early signs of infection for intravenous access. Our FRAM analysis has been non-normative: performance variability is not necessarily wanted or unwanted, it is merely necessary where system contradictions cannot be easily resolved and so adaptive capacity is required to cope. Highlights: Different styles of FRAM analysis are recognised. The style of FRAM explored here focuses on contradictions inherent in the system. System contradictions lead to performance variability, e.g. in infusion administration. Adaptive capacity is needed where contradictions cannot be easily resolved. Adaptive capacity for infusion administration needs to be enhanced, not eroded.